Application of Arduino in Measuring, Monitoring, and Analyzing the Performance of Home Solar Panel - ferdinand; boediardjo, kirina; sinaga, maralo (Liaison Journal of Engineering, 2023)
Solar panels are commonly used to replace power sources like fossil fuel. The usage of solar panels is because it is eco-friendly to the environment and can keep producing electricity freely as long as there is sun ‘s light. Although there is a downside for solar panels, it is still a safe choice for producing or replacing any kind of power source. This research gives the details related to solar panel power and includes the usage of the solar panel to the household appliance. The main content of this paper is monitoring, analyzing, measuring Solar PV panel DC power output and using Arduino based modules to do the monitoring, analyzing, measuring for this research. After the measuring and analyzing the output, this result can give the researcher to achieved and accurate result of the DC power output of the solar panel and can be used for industrial purposes and household appliances and also monitoring that are created on LCD can be used for maintenance if there is in need for maintenance, so that the power output can be check all the time automatically without physical interference. Keywords: Solar Panel, DC power, Monitoring, Analyzing, Measuring, Arduino.